Breeding for improving fibre yield and green biomass in sunnhemp (Crotalaria juncea L.) germplasm (Bangladesh Journal of Agricultural Research, 2012)
Fifteen genetically diverse parental genotypes of sunnhemp belonging to different geographical origin were assessed to evaluate general and specific combining ability of parents and cross combinations, respectively, for selecting the superior parent combination. For this, fifteen parents and their 105 F1s were grown in a Randomized Block Design (RBD) with three replications and data were collected in respect of plant height, base diameter, green weight, fibre weight, stick weight and fibre percentage. Analyses of variances of diallel revealed that there was predominance of specific combining ability (sca) in almost all the characters except fibre percentage and general combining ability (gca) was significant only in case of plant height. From the gca effect of parents it can be seen that K-12 (B) and SUIN-056 showed good promise as general combiners and able to produce better cross combinations. However only one cross combination viz. SUIN056 × SUIN074 was recorded positive sca effects for all the characters. This cross combination along with SUIN001 × SUIN056 exhibited positive heterosis over the better parents in all the characters studied and can be used in breeding programme for producing improved sunnhemp population. Further, to exploit fully both additive and nonadditive variances present in this population, random as well as chain crossing among the promising crosses was found effective to exploit both additive and fixable epistatic effects. Bangladesh J. Agril. Res. 37(3): 369-376, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12080